INFLUENCE OF PBL SETS TO INCREASE STUDENT LEARNING OUTCOME AND ACTIVITIES IN CLASS VIII ON LIQUID PRESSURE MATERIAL AT SMP NEGERI 35 MEDAN - Siti Aisyah; Nora Susanti; Sri Mulyani (UNIVERSITAS NEGERI MEDAN, 2022)
This research aims to determine the influence of the application of PBL SETS learning model on the learning outcomes of class VIII SMP Negeri 35 Medan and to determine the influence of the application of the PBL SETS learning model on the student learning activities of class VIII students of 35th junior high school Medan. The Research type used was quasi-experimental type. The sample of this study was 60 students of class VIII 35th junior high school Medan. The experimental class was class VIII5 and control class was VIII6 . The instrument of research used was in the form of 10 items of essay questions and student activity observation sheets. The design of research used is the Nonequivalent Control Group design. The Research data collection techniques used were test and observation. The results of this study indicated a significant influence on learning outcomes of student. The average of student learning outcome in experimental class was greater than in the control class, namely the experimental class value was 73.83 and the control class value was 44.9. The results of the t-test independent samples test showed that the two-tailed significance <0.005. The results of data analysis showed the implementation of the PBL SETS learning model and approach can increase student learning outcomes in class VIII of SMP Negeri 35 Medan on the subject of Pressure in Liquids and the application of the PBL SETS learning model can improve the learning activities of class VIII students of 35th junior high school Medan on the material Pressure on Liquids.